The isolation of Gurnbiro virus from larvae and darkling Ivelles (Carcinops pumilin) - Parede, Lies; Indriani, Risa; ., Sukarsih (Indonesian Animal Sciences Society, 1996)
Gumboro (infectious bursal disease, IBD) virus was isolated from darkling beetles (Carrinaps pumilin) and their larvae in a commercial pulletchicken farm with repeated outbreaks incidence of Gumboro disease in Tangertng, West Java. In addition, these over populated beetles and their larvae were suspected to be infected and then shed the virus or acted as vectors. Isolation was done by repeated passages of virus using chicken embryo fibroblast cells as prime media, which then showed the evidence of cylop: ihic effecis. The isolation was followed by antigen detection by means of ELISA test. Â Key words: Gumboro disease, infectious bursal disease, darkling beetle, Carcinops punulin Â